Implementation of Convention on The Rights of Persons with Disabilities in Providing Legal Protection for Persons with Disabilities in Indonesia - Yuliartini, Ni Putu Rai; Dewi, Anak Agung Istri Atu; Darmawan, Ni Ketut Supasti (Universitas Negeri Malang, 2021)
The purpose of this study was to analyze legal protection for persons with disabilities in Indonesia and the implementation of the convention on the rights of persons with disabilities in Indonesia. The approach used in this research was a qualitative approach with a descriptive analysis method. The type of research used normative juridical. Data collection techniques used literature study. The results of the study indicated that legal protection for persons with disabilities in Indonesia had been included in the constitution and several laws and regulations. The principles of equality and non-discrimination were contained in several instruments. The existence of special rights granted to persons with disabilities to be able to maintain their identity, characteristics, and traditions. Non-discriminatory treatment was equally important to achieve equal treatment. The implementation of the convention on the rights of persons with disabilities in Indonesia was evidenced by the ratification of Law Number 19 of 2011 concerning Ratification of the Convention on the Rights of Persons with Disabilities. Providing equal opportunities for persons with disabilities in all aspects of state and community administration, respecting, protecting, and fulfilling the rights of persons with disabilities, including the provision of adequate accessibility and accommodation aimed at protecting from neglect, exploitation, harassment, all discriminatory actions, and violations of human rights.